Agenda 2030 e o papel social da biblioteca universitária: uma reflexão em torno dos serviços de informação frente à diversidade dos estudantes cotistas no ensino superior - Batista Zaninelli, Thais (2025)
The study delves into the evolving services of University Libraries to meet the diversity of the university community that enters higher education through the quota system, that is, through affirmative action policies within the context of the Sustainable Development Goals of the 2030 Agenda. To identify the information services tailored for students entering higher education via affirmative actions, contextualized within the Sustainable Development Goals of the 2030 Agenda. The research was based on a theoretical framework carried out in Information Science databases covering the literature from 2012 to 2023. Some actions are already being developed by libraries, reinforcing their pivotal social role. There are a variety of user groups served by inclusive information services. However, while some of these services are offered by non-academic libraries, the potential exists for adaptation and incorporation within the university library environments. Studies centered on affirmative actions within the scope of the inclusive university library, the Sustainable Development Goal and the 2030 Agenda are gaining traction. However, these three areas remain unexplored in the context of Information Science research, which is the main contribution of this article.